2012
DOI: 10.5121/ijasuc.2012.3408
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Various Routing Protocols in Different Mobility Models

Abstract: Mobile Ad hoc Network (MANET) is a infrastructure less network in which two or more devices have wireless communication which can communicate with each other and exchange information without need of any centralized administrator. Each node in the ad hoc network acts as a router, forwarding data packets for other nodes. The main issue is to compare the existing routing protocol and finding the best one. The scope of this study is to test routing performance of three different routing protocols (AODV, OLSR and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The authors in [23] have compared the performance of AODV, OLSR and DSDV with respect to reference point group mobility and random waypoint mobility models. It is found that, in the case of random waypoint mobility model, AODV shows maximum packet delivery ratio, least routing load and MAC load.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [23] have compared the performance of AODV, OLSR and DSDV with respect to reference point group mobility and random waypoint mobility models. It is found that, in the case of random waypoint mobility model, AODV shows maximum packet delivery ratio, least routing load and MAC load.…”
Section: Related Workmentioning
confidence: 99%
“…All nodes that are connected will be updated in each of the node's table to maintain the configuration of the protocol and were shared among themselves. Therefore, if there are any changes in the network topology, each node will update its routing table [7]. These types of routing are applied in the link-state routing and distance vector routing.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Seminal examples of RWP use are found in Perkins et al, 2001, [76] and Boukerche, 2004, [113]. Its continual use is cited in Uzoh'et al, 2012, [114], Sharma and Mukherjee, 2012, [115], and Rani et al, 2012, [116]. It is common to use RWP as a baseline when discussing realistic mobility models.…”
Section: The Random Way Point Model (Rwp)mentioning
confidence: 99%